Exploring the Role of Economic and Digital Literacy in Shaping Entrepreneurial Behavior in Online Business Platforms - Mardiatul Jannah (Pinisi Journal of Entrepreneurship Review, 2024)
This study explores the influence of economic and digital literacy on entrepreneurial behavior among business actors registered on the Grab application. Utilizing a quantitative approach, the research draws on primary data collected from respondents to analyze the relationship between these literacy levels and entrepreneurial behavior. The analysis methods include descriptive and statistical analyses, such as multiple linear regression, hypothesis testing, and correlation analysis. The findings indicate a positive and significant relationship between economic literacy and digital literacy on entrepreneurial behavior. This suggests that a solid understanding of economic principles, coupled with effective use of digital technology, plays a crucial role in shaping the entrepreneurial behavior of business actors in Makassar City, particularly those in the culinary sector. The study highlights the importance of enhancing both economic and digital literacy to foster entrepreneurial success. Business actors are encouraged to participate in training and literacy programs to develop the necessary knowledge and skills that will enable them to thrive in the competitive business environment.